Preservation of Antegrade Pulmonary Blood Flow in Kawashima Procedure With Prior Right Ventricular Outflow Tract Stent. Issue 4 (July 2022) - Bhansali, Suneet; Bhatla, Puneet; Argilla, Michael; Saharan, Sunil; Mosca, Ralph; Kumar, TK Susheel
Surgical management of single ventricle with interrupted inferior vena cava and azygos continuation typically requires a Kawashima procedure with subsequent completion of Fontan. However, this group is at risk of development of pulmonary arteriovenous malformations. Evidence suggests preservation of hepatic venous flow into the pulmonary circulation can potentially delay this development. We hereby describe a method of preserving antegrade pulmonary blood flow during the Kawashima procedure in the setting of prior right ventricular outflow tract stents.